A Meningococcal Outer Membrane Vesicle Vaccine Incorporating Genetically Attenuated Endotoxin Dissociates Inflammation from Immunogenicity - Dowling, David J.; Sanders, Holly; Cheng, Wing Ki; Joshi, Sweta; Brightman, Spencer; Bergelson, Ilana; Pietrasanta, Carlo; van Haren, Simon D.; van Amsterdam, Sandra; Fernandez, Jeffrey; van den Dobbelsteen, Germie P. J. M.; Levy, Ofer (Frontiers in Immunology, 2016)
Background. Group B Neisseria meningitidis, an endotoxin-producing gram-negative bacterium, causes the highest incidence of group B meningococcus (MenB) disease in the first year of life. The Bexsero vaccine is indicated in Europe from 8 weeks of age. Endotoxin components of outer membrane vesicles (OMVs) or soluble lipopolysaccharide (LPS) represent a potential source of inflammation and residual reactogenicity. The purpose of this study was to compare novel candidate MenB vaccine formulations with licensed vaccines, including Bexsero, using age-specific in vitro culture systems. Methods. OMVs from wild type and inactivated lpxL1 gene mutant N. meningitidis strains were characterized in human neonatal and adult in vitro whole blood assays and dendritic cell arrays. OMVs were benchmarked against licensed vaccines, including Bexsero and whole cell pertussis formulations, with respect to Th-polarizing cytokine and PGE2 production, as well as cell surface activation markers (HLA-DR, CD86, CCR7). OMV immunogenicity was assessed in mice. Results. ΔlpxLI native OMVs demonstrated significantly less cytokine induction in human blood and DCs than Bexsero and most of the other pediatric vaccines (e.g., PedvaxHib, EasyFive, Bacillus Calmette–Guérin (BCG)) tested. Despite a much lower inflammatory profile in vitro than Bexsero, ΔlpxLI native OMVs still had moderate DC maturing ability and induced robust anti-N. meningitidis antibody responses after murine immunization. Conclusions. A meningococcal vaccine comprised of attenuated LPS-based OMVs with a limited inflammatory profile in vitro induces robust antigen-specific immunogenicity in vivo.